LENGTH-WEIGHT RELATIONSHIP IN THE SNAPPER, LUTIANUS KASMIRA (FORSKAh) - Rengarajan, K (Indian Journal of Fisheries, 2011)
The length-weight relationship in Lutianus kasmira has been worked outffoih samples collected at Fori BMr, "Andamans during the years-t966"68. Thevalue of the exponent 'o' in the parabolic equation was found to be very nearly3.0. The relation between length and weight in this species could be expressedby the hypothetical cube law. The observed and calculated weights for the correspondinglengths showed a close relationship. No significant variation in theregression coefficfent was noticed between the two sexes or betweeir the years.^